VALUES OF VERBAL PREFIXES IN SLOVENIAN (Philological Studies, 2019)
In the article the process of gradual weakening of spatial lexical meaning of verbal prefixes which took place in late Proto-Slavic is discussed. Consequently, in the Slavic languages three types of verbal prefix meaning occur (i.e. spatial meaning, lexical and grammatical aspect). Following this methodological frame, the existing typology of verbal prefix meanings of prefixed verbs with non- lexicalized meaning in Slovene is presented.
Keywords: semantic change, weakening of lexical meaning, verbal prefix, lexical aspect, grammatical aspect, Slovene